2016
DOI: 10.18632/oncotarget.12489
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor 1 gene variants are associated with high-altitude pulmonary edema risk

Abstract: Previous studies demonstrated that Angiotensin II Receptor 1 (AGTR1) may play an important role in the development of high-altitude pulmonary edema. We envisaged a role for AGTR1 gene variants in the pathogenesis of HAPE and investigated their potential associations with HAPE in a Han Chinese population. We genotyped seven AGTR1 polymorphisms in 267 patients with diagnosed HAPE and 304 controls and evaluated their association with risk of HAPE. Statistically significant associations were found for the single n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Disturbance of the RAAS is attributed, in part, to genetic variants in at least five critical genes namely REN, AGT , ACE, AGTR1 , and CYP11B2 . 20 , 49 53 Of these, the major genetic variants that have been associated with HAPE are rs4762 (Thr207Met) and rs699 (Met268Thr) of AGT , 53 , 54 the insertion/deletion (indel) alleles (I/D, 287bp alu repeat sequence), rs8066114 and rs4461142 of ACE , 20 , 50 , 51 , 53 , 55 rs275651 and rs275652 of AGTR1 , 56 and –344T/C and intron 2 conversion of CYP11B2 ( Fig. 1 and Table 1 ).…”
Section: Renin–angiotensin–aldosterone System-mediated Allele-specifimentioning
confidence: 99%
“…Disturbance of the RAAS is attributed, in part, to genetic variants in at least five critical genes namely REN, AGT , ACE, AGTR1 , and CYP11B2 . 20 , 49 53 Of these, the major genetic variants that have been associated with HAPE are rs4762 (Thr207Met) and rs699 (Met268Thr) of AGT , 53 , 54 the insertion/deletion (indel) alleles (I/D, 287bp alu repeat sequence), rs8066114 and rs4461142 of ACE , 20 , 50 , 51 , 53 , 55 rs275651 and rs275652 of AGTR1 , 56 and –344T/C and intron 2 conversion of CYP11B2 ( Fig. 1 and Table 1 ).…”
Section: Renin–angiotensin–aldosterone System-mediated Allele-specifimentioning
confidence: 99%
“…This gene encodes the angiotensin II receptor 1 (AT 1 R), and polymorphisms in AGTR1 have been suggested to be involved in the physiological response to hypoxia [62]. AT 1 R is broadly expressed in different tissues and mediates most of the classical actions of angiotensin II, including vasoconstriction and vascular smooth muscle cell proliferation [63]. Thus, under hypoxic conditions, angiotensin II engages AT 1 R to modulate the pulmonary vasoconstrictive response [64].…”
Section: Discussionmentioning
confidence: 99%
“…heart rate and respiratory rate) required for the diagnosis of HAPE so that their results could be compared with other genetic studies carried out on HAPE. 3,4 He et al 1 reported that none of the subjects of control group (who had same ascent rate and altitude as achieved by the HAPE cases) developed signs and symptoms of HAPE within 7 days of exposure to high altitude. The basis of choosing a '7-day' period of observation for the control group is not clear because HAPE is known to occur mostly 2-4 days after reaching an altitude of 3000 m or more.…”
Section: Risk Of High Altitude Pulmonary Edema and Telomere Lengthmentioning
confidence: 99%
“…It would have been appropriate for He et al to have also included other important parameters (e.g. heart rate and respiratory rate) required for the diagnosis of HAPE so that their results could be compared with other genetic studies carried out on HAPE . He et al reported that none of the subjects of control group (who had same ascent rate and altitude as achieved by the HAPE cases) developed signs and symptoms of HAPE within 7 days of exposure to high altitude.…”
mentioning
confidence: 99%